Altered Cortisol Metabolism Increases Nocturnal Cortisol Bioavailability in Prepubertal Children With Type 1 Diabetes Mellitus - Brossaud, Julie; Corcuff, Jean-Benoît; Vautier, Vanessa; Bergeron, Aude; Valade, Aurelie; Lienhardt, Anne; Moisan, Marie-Pierre; Barat, Pascal (Frontiers in Endocrinology, 2021)
Objective: Disturbances in the activity of the hypothalamus-pituitary-adrenal axis could lead to functional alterations in the brain of diabetes patients. In a later perspective of investigating the link between the activity of the hypothalamus-pituitary-adrenal axis and the developing brain in children with diabetes, we assessed here nocturnal cortisol metabolism in prepubertal children with type 1 diabetes mellitus (T1DM). Methods: Prepubertal patients (aged 6–12 years) diagnosed with T1DM at least 1 year previously were recruited, along with matched controls. Nocturnal urine samples were collected, with saliva samples taken at awakening and 30 minutes after awakening. All samples were collected at home over 5 consecutive days with no detectable nocturnal hypoglycaemia. The State-Trait Anxiety Inventory (trait scale only) and Child Depression Inventory were also completed. Glucocorticoid metabolites in the urine and salivary cortisol (SC) were measured by liquid chromatography–tandem mass spectrometry. Metabolic data were analysed by logistic regression, adjusting for sex, age, BMI and trait anxiety score. Results: Glucocorticoid metabolites were significantly lower in T1DM patients compared to controls. 11β-hydroxysteroid dehydrogenase type 1 activity was significantly higher, while 11β-hydroxysteroid dehydrogenase type 2, 5(α+β)-reductase and 5α-reductase levels were all lower, in T1DM patients compared to controls. There was no significant group difference in SC level at the time of awakening or 30 minutes thereafter. Conclusions: Our findings suggest that altered nocturnal cortisol metabolism in children with T1DM leads to greater cortisol bioavailability and lower cortisol production as a compensatory effect. This altered nocturnal glucocorticoid metabolism when cortisol production is physiologically reduced questions its impact on brain functioning.